Ishimozuku (Sphaerotrichia firma) lipids containing fucoxanthin suppress fatty liver and improve short chain fatty acid production in obese model mice - Shibata, Masaki; Fukuda, Satoru; Terasaki, Masaru; Maeda, Hayato (Frontiers in Sustainable Food Systems, 2024)
Ishimozuku (Sphaerotrichia firma) is one species of edible brown algae in Japan. The lipids contain rich of fucoxanthin and n-3 unsaturated fatty acids. This study analyzed dietary Ishimozuku lipid components and the effects on fatty liver and intestinal metabolite component production in obese model mice. Ishimozuku lipids contained fucoxanthin about 44.71± 0.02 mg/g. KK-A y mice were fed with high-fat diet (Control) and a high-fat diet + 0.5% Ishimozuku lipid diet (Ishimozuku) for 4 weeks. Liver triglyceride contents and serum triglyceride concentrations were significantly lower in the Ishimozuku group than in the Control group. Results show that acetyl-CoA carboxylase (ACC) and stearoyl-CoA desaturase (SCD-1) mRNA expression were suppressed in the livers of Ishimozuku group mice. Furthermore, short chain fatty acid amounts in the cecal contents were greater in the Ishimozuku group mice. These results suggest that dietary Ishimozuku lipid components suppress liver lipid accumulation. Results also indicate Ishimozuku lipid components improve the balance of the intestinal microflora, which is disturbed by a high fat diet, and which promotes short chain fatty acid accumulation in the intestine. That accumulation is related to lipid and glucose metabolism.